The correlation of region-specific lifestyle and subjective perception of oral health with oral health-related quality of life among Tibetan early adolescents in Ganzi: a cross-sectional study - Shaoying Duan; Renjie Tang; Chenchen Zhang; Qianqian Su; Huiyu Yang; He Cai; Tao Hu (PeerJ)
Background The oral health-related quality of life (OHRQoL) of Tibetan adolescents has been largely overlooked. Aim This cross-sectional study examined the association of region-specific lifestyle, subjective perception, and clinician conditions of oral health with Tibetan adolescents’ OHRQoL in Ganzi, Sichuan. Methods The OHRQoL was measured using standardized Child Oral Impacts on Daily Performances (sC-OIDP) scores. Binary logistic regression was used to explore the association between region-specific lifestyle, subjective perception of oral health, clinician oral health conditions (gingival bleeding on probing (BOP), dental calculus (DC), and decayed, missing, and filled teeth (DMFT)), and OHRQoL. Results In total, 485 Tibetan adolescents were included. In relation to region-specific lifestyle, the factors associated with poorer OHRQoL were residence altitude of 3,300 m (compared to 1,400 m), buttered tea consumption by adolescents or mother, and being a boarding student. Regarding the subjective perception of oral health, adolescents that rated bad or very bad oral health or self-reported dental pain had poorer OHRQoL. Interestingly, clinician oral health conditions were not related to OHRQoL. Conclusions This study underscores the relationship between region-specific lifestyle, subjective oral health perceptions, and OHRQoL among Tibetan adolescents. Addressing these factors through tailored health initiatives can play a pivotal role in improving oral health outcomes and overall quality of life in remote regions like Ganzi. Future research should focus on longitudinal studies to better understand the causality and long-term impact of targeted interventions.